Cryptorchidism Is Frequently Associated With Testicular Dysfunction - Rey, Rodolfo Alberto (2024)
Cryptorchidism or undescended testis, that is, testis that is not located at or below mid-scrotum, is one of the most common congenital abnormalities in newborns, with a prevalence between 1.6% and 9.0%, according to different series [1]. Additionally, acquired cryptorchidism, or ascensus testis, refers to postnatal testicular ascent occurring when the cremasteric reflex is established [1]. In sum, cryptorchidism is a frequent reason for seeking medical attention in pediatric age...